2020
DOI: 10.1002/ange.202011482
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Interfacial Chemistry in Lithium‐Ion Batteries by a Weakly Solvating Electrolyte**

Abstract: The performance of lithium-ion battery is highly dependent on its interfacial chemistry, which is regulated by electrolytes. Conventional electrolyte typically contains polar solvents to dissociate Li salts. Here, we report a novel weakly-solvating electrolyte (WSE) that consists of a pure non-polar solvent, which leads to a peculiar solvation structure where ion pairs and aggregates prevail under a low salt concentration of 1.0 M. Importantly, WSE forms unique anion-derived interphases on graphite electrodes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 47 publications
6
31
0
Order By: Relevance
“…Moreover, the Li 2 CO 3 crystallites with decreased size generates more contact interface of Li 2 CO 3 and Li 2 O, attributing to form more phase boundaries and vacancies, which may exhibit a more aggressive synergetic effects for facilitating Li‐ion transport. [ 21–22 ] EDS mapping results are consistent to support the HRTEM results as shown in the C and O signal distributions in Figure 3 and Figures S8–S10 (Supporting Information). Distinct from the basis HC, the O signals that are mainly originated from the SEI are enriched at the outer shell of HC particles.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Moreover, the Li 2 CO 3 crystallites with decreased size generates more contact interface of Li 2 CO 3 and Li 2 O, attributing to form more phase boundaries and vacancies, which may exhibit a more aggressive synergetic effects for facilitating Li‐ion transport. [ 21–22 ] EDS mapping results are consistent to support the HRTEM results as shown in the C and O signal distributions in Figure 3 and Figures S8–S10 (Supporting Information). Distinct from the basis HC, the O signals that are mainly originated from the SEI are enriched at the outer shell of HC particles.…”
Section: Resultssupporting
confidence: 83%
“…Moreover, the Li 2 CO 3 crystallites with decreased size generates more contact interface of Li 2 CO 3 and Li 2 O, attributing to form more phase boundaries and vacancies, which may exhibit a more aggressive synergetic effects for facilitating Li-ion transport. [21][22] EDS mapping results are consistent to support the HRTEM results as shown in the C and O signal distributions in Figure 3 the formed organic-rich and Li 2 CO 3 -rich SEI can both completely wrapping the HC boundary. As comparison, a larger, distinguished but intermittent O signals are collected in the SEI formed under MOP, indicating the formed SEI structures are thick but discontinued.…”
Section: Characterization Of Sei Layers Formed Under Different Potent...supporting
confidence: 83%
See 1 more Smart Citation
“…This behavior can be explained by Zhangs work on aweakly-solvating electrolyte (WSE). [24] When 0.4 m LiNO 3 is added to the 0.2 mL iTFSI + DME/MPE, the peak of Li + -TFSI À disappears because the NO 3 À displaces the TFSI À from the Li + solvation sheath due to the high donor number of NO 3 À .Atthe same time,apositive deviation of the NO 3 À peak, derived from the coordination of NO 3 À to Li + , was observed in the ultralight electrolyte (Figure S8a). It should be noted that TFSI À was re-involved in the solvation sheath when the LiNO 3 was reduced to 0.2 m( Figure S8b); this indicated that LiNO 3 enhanced the dissociation of LiTFSI in weakly coordinating solvents due to its high donor number.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the conventional electrolyte, am ore pronounced LiF peak was found in the ultralight electrolyte resulting from the reduction of TFSI À on the lithium surface.This was attributed to the fact that the solvent activity is greatly decreased by the addition of the weakly solvating MPE, and LiNO 3 and LiTFSI would be preferentially reduced on the lithium surface.M oreover,L iNO 3 can promote the decomposition of LiTFSI, forming LiF. [24,25] Figure 5d-I shows that the deposited lithium morphologies are highly dependent on the deposited capacities and the electrolytes. At alow deposition capacity of 0.25 mAh cm À2 in the conventional electrolyte,t he Li deposition follows the island growth model, where irregular lithium randomly deposits to form isolated particles (Figure 5d).…”
Section: Angewandte Chemiementioning
confidence: 99%